(untitled) (International journal of artificial intelligence, 2025)
This article discusses the development of cognitive skills of children aged 5-7 years through creative activities, and the problems of various activities carried out with them. It also discusses their curiosity; their constant search for answers to various questions; the rapid development of thinking, perception, imagination, memory, as well as drawing, application, theatrical roles, musical activities, which develop high-level cognitive skills and master new ideas, creative thinking and problem-solving skills. The author emphasized in the article the need to improve methods that effectively affect the formation of cognitive activity in preschool children in the development of cognitive skills. If the cognitive skills of a preschool child are developed through creative activities, the child's mental potential, thinking speed, intellectual ability (IQ) develops.